Pozamilitarne aspekty bezpieczeństwa współczesnego świata – problem starzenia się społeczeństw - Nowiak, Wojciech (Przegląd Strategiczny, 2016)
There is no doubt that the rapid increase in population aging across the globe is signaling the most astonishing demographic changes in the history of humankind. Demographic changes are among the most important challenges facing societies, labour markets and economies. This paper analyzes how low fertility rates, aging populations, and a growing number of migrants from other countries change the face of our globe and created the new threat to national security.